2016
DOI: 10.1097/qai.0000000000001092
|View full text |Cite
|
Sign up to set email alerts
|

Baseline CD4 Count and Adherence to Antiretroviral Therapy: A Systematic Review and Meta-Analysis

Abstract: This review was unable to find consistent evidence of differences in adherence according to baseline CD4 count. Although this is encouraging for the new recommendations to treat all HIV-positive individuals irrespective of CD4 count, there is a need for additional high-quality studies, particularly among adults initiating ART at higher CD4 cell counts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 48 publications
(117 reference statements)
4
19
0
Order By: Relevance
“…Our cohort comprised individuals with a higher median CD4 count at ART initiation than in those studies and findings corroborate that seen in high income countries reported in the systematic review by Bock et al. . WHO recommends universal test and treat for HIV ; South Africa has already adopted this recommendation but there are no data on adherence in people initiating ART at high CD4 counts (CD4 > 350) in the African setting.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Our cohort comprised individuals with a higher median CD4 count at ART initiation than in those studies and findings corroborate that seen in high income countries reported in the systematic review by Bock et al. . WHO recommends universal test and treat for HIV ; South Africa has already adopted this recommendation but there are no data on adherence in people initiating ART at high CD4 counts (CD4 > 350) in the African setting.…”
Section: Discussionsupporting
confidence: 85%
“…With the new treatment guidelines, the median CD4 count at which individuals initiate ART is likely to rise to levels observed in our cohort. However, a meta-analysis covering the period from January 2002 to Dec 2013 showed that the CD4 count at presentation for HIV care has increased in South Africa but the CD4 count at ART initiation has remained unchanged at a mean of 123 cells/mm 3 [18].…”
Section: Discussionmentioning
confidence: 99%
“…In both studies, the reference group comprised individuals with advanced HIV disease based on the reported median CD4 count at ART initiation. Our cohort comprised individuals with a higher median CD4 count at ART initiation than in those studies and findings corroborate that seen in high income countries reported in the systematic review by Bock et al [17]. WHO recommends universal test and treat for HIV [1]; South Africa has already adopted this recommendation Using either adherence measure, men had more than double the odds of sub-optimal adherence compared with women, similar to findings reported in two studies in Tanzania [19] and South Africa [20].…”
Section: Discussionsupporting
confidence: 79%
“…The International Antiviral Society‐USA guideline also recommended initiating ART in all HIV+ adults in 2012 . Although HIV+ persons in recent periods have likely initiated ART at a higher CD4 count on average than those in earlier periods , a recent systematic review found no consistent association between baseline CD4 count and ART adherence in routine clinical settings . When we separately examined patients who initiated ART in 2012 (Table , implementation rate during persistent episode), the estimate of ART implementation rate and its trend remained similar between those in 2012 and those in the immediately preceding years.…”
Section: Discussionmentioning
confidence: 76%